OPTIMALISASI KUALITAS LAYANAN DAN PRODUK BANK MUAMALAH PROBOLINGGO - Hidayat, Rahmad; Pertiwi, Fia Ayuning (JSE: Jurnal Sharia Economica, 2022)
Bank Muamalat is a bank that operates on Islamic principles in its transactions, unlike conventional banks that usually operate using conventional methods. Competitiveness between the two types of banks in terms of services and products provided by banks is an aspect that needs to be considered as a focal point for customers. The Muamalat Bank was established in accordance with the Shariah with the implementation of Islamic principles that encourage a targeted approach to customers.This research method uses a qualitative method by taking some of the simplicities that have already come from some bank customers who have savings and conduct transactions.The results of the discussions the Bank evaluates and escalates to be intensive in its use. Comprenshif towards customers ranging from the middle and above adaptive with the development of the era that builds products with fully based digital technology not only the needs of transactions at the bank but also other needs are more flexible and convenience for the customers. Positive customer ratings in terms of services and products play a significant role in the needs of customer transactions that are probolinggo society Keybroad : Product quality, Satisfaction, Service Quality, Customer Loyalty